If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy + 3 = 0 Reorder the terms: 3 + xy = 0 Solving 3 + xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + xy = 0 + -3 Combine like terms: 3 + -3 = 0 0 + xy = 0 + -3 xy = 0 + -3 Combine like terms: 0 + -3 = -3 xy = -3 Divide each side by 'y'. x = -3y-1 Simplifying x = -3y-1
| k/72=0.8 | | 8(1-5n)+8n=200 | | 13.1=h+6.2 | | -6+25=m-10 | | -12=p-2 | | -2(5k-3)=86 | | 170m=1.54 | | -55x-20=0 | | 6+2p=10 | | 2c^2+5c+2=0 | | 3x-12+6=0 | | 170=1.54 | | 8a+3a=132 | | 18-b=13 | | 1-2/3y=12/5-1y/5 | | 7c+2c-8c=17 | | 8(1+5x)=-312 | | 3(3+5x)=2/3+3/7x | | -12a+3a=9 | | a+5=0.2(15+5a) | | -8(1+6v)=-104 | | x-1025=-2 | | 1.2(x-8)=1.9(x-1) | | x+66=14 | | 15m-6m-2m=14 | | -20x+5y=60 | | 6x-7=x-8 | | (60x^4)-(60x^2)=0 | | 7m-7(5m+2)=154 | | 5x-1=6-2x | | 8x^-8/30x^9 | | 5(3+p)=-10 |